Possible Role of Drug Interactions in Bupivacaine-induced Problems Related to Intraventricular Conduction Disorders. Issue 4 (July 1990) - Timour, Q.; Loufoua, J.; Faucon, G.; Freysz, M.; Bertrix, L.; Couzon, P.; Gerentes, I.
Abstract : Clinically, bupivacaine has depressant effects on intraventricular conduction that may lead to serious atrioventricular blocks or reentrant arrhythmias at plasma levels below those required to produce these effects experimentally (2-3 μg/ml instead of 8-10 μg/ml). The difference could be due to drugs present in the blood at the time of regional anesthesia that similarly inhibit conduction. This hypothesis was examined in 30 anesthetized, closed-chest dogs by measuring conduction time in the ventricular contractile fibers as well as effective refractory period under pacing at a constant, relatively high (180 beats/minute) rate. Changes in sinus rate were limited, as well as changes in ventricular effective refractory period and blood pressure regardless of the drug tested. In contrast, cibenzoline, disopyramide, and propranolol increased conduction time and lengthened QRS duration. Clomipramine appeared to prolong conduction time and widen QRS only moderately in therapeutic doses, whereas verapamil did not manifest noticeable effects on conduction. Caution is therefore recommended in regional anesthesia with bupivacaine in subjects being treated with cardiovascular drugs, such as cibenzoline, disopyramide, and propranolol and their congeners, or even by tricyclic antidepressants.